Effects of Real Exchange Rate on Trade Balance: Empirical Evidence from Nigeria - AKPANSUNG, Aniekan Okon; BABALOLA, Sikiru Jimoh (Asian Journal of Empirical Research, 2013)
The paper empirically examines the effects of real exchange rate on trade balance in Nigeria. The econometric diagnostics for presence of unit roots in the series was conducted using the Augmented Dickey-Fuller technique. The results indicate that all the variables are integrated of order one while the major Error Correction terms (